Nursing Intervention based on art therapy for Caregivers of Older Adults with Alzheimer's - Guerrero Castañeda, Raúl Fernando (2023)
Alzheimer's disease (AD) is made up of a group of memory progression disorders, mainly, but with impairments in other cognitive functions that lead to functional decline that progressively reduces autonomy in people who suffer from it. Since the diagnosis of Alzheimer's in the elderly, care has been explicit, initiating a series of changes in the family, which range from assuming a new role to emotional and economic transitions. The caregiver is hardly cared for, most care strategies are aimed at training the caregiver for care. There are several non-pharmacological techniques such as art therapy, however, they are oriented towards the patient suffering from the disease, not the caregiver. Art therapy can be implemented by nursing staff in order to enhance the communication and expression of emotions of caregivers, therefore the objective is to propose a nursing intervention based on art therapy for caregivers of older adults with Alzheimer's.